Holiday playbook - St. John, Yahrah (Harlequin desire, 2021)
All marketing executive Giana Lockett wants for Christmas is to land an endorsement deal with Wynn Starks' sports drink company. It's tough being the baby girl in a family of alpha men, and this will finally prove her worth to the Locketts' Also tough? Securing a meeting with Atlanta's most elusive billionaire. Giana's not giving up, and once she makes contact, the prize gets closer- and so does Wynn's bed. The chemistry between her and Wynn is hot. But business is business, until pleasure changes all the rules.